Coristoma ósseo mesentérico em uma porca - Takeuti, Karine Ludwig; Fredo, Gabriela; Viott, Rafael Cé; Driemeier, David; Barcellos, David Emílio Santos Neves (Acta Scientiae Veterinariae, 2017)
Background: Osseous choristomas represent the production of osseous tissue in abnormal regions, such as subcutaneous, fibrous or perivascular tissues, skeletal muscle and skin. These structures have been found in humans, dogs (lungs and dura mater), horses (large intestines) and cattle (lungs and mesenteric lymph nodes). They were also found in the mesenteric region and thoracic cavity of sows and piglets. The aim of this paper was to describe the macro and microscopic lesions found in a sow which died suddenly by a rare mesenteric osseous choristoma. Case: A lactating sow, parity four, from the Swine Department of the Federal University of Rio Grande do Sul (UFRGS), Brazil, showed appetite loss, hyperthermia (41.5ºC) and sudden death. The animal was submitted to necropsy at the Department of Veterinary Pathology, UFRGS. On external examination, the sow showed conjunctival and perioral cyanosis, proximal colon region with a firm structure with approximately 3.0 cm length in mesenteric area. Moreover, the colon was ruptured and fibrin deposition and intestinal content in abdominal cavity were observed. Fragments of organs were collected in 10% formalin, routinely processed for histology and colored with hematoxylin and eosin stain (H&E). Histologically, it was found bone trabeculae with osteoid, periosteum, spaces with osteocids and endochondral ossification with bone marrow composed by adipose tissue and intense proliferation of conjunctive stroma. The mesenteric lymph nodes showed intense lymphoid hyperplasia with multifocal centrilobular necrosis. There was fibrin in serosa of colon, acute peri-spleen and acute fibrinopurulent perihepatitis. Discussion: Macroscopic and microscopic findings were consistent with mesenteric osseous choristoma. This condition is unusual in domestic animals, however it has been already described in pigs. Osseous choristoma could be related to previous mesenteric torsions, which could occur in growing phase, causing inflammation and hemorrhage, stimulating its generation. These structures may cause lesions in adjacent organs. The abrupt movements of the sow or intestinal peristalsis could have broken the bone, raising two tips, which in contact with the colon, ruptured it. Because of this, shedding of intestinal content was observed, which resulted in an acute peritonitis and sudden death of the animal. The annual mortality rates of sows (natural deaths or euthanasia) varies from 4.0 to 6.0%, but may be variable. Sow sudden deaths represent 17.5% of all sows and boars deaths, and gilts, pregnant and lactating sows are more susceptible. The most common causes of sow sudden death are gastrointestinal problems, such as ulcer, enteritis, torsions and ruptures; pneumonia; urinary infections, such as cystitis and pyelonephritis; heart failure; dystocia, and septicemia. However, one third of sudden death causes are not identified. The necropsy is the only way to identify the cause of death, through observation of macroscopic lesions and subsequent laboratory tests. Better knowledge of causes is important to establish control measures and possibly reduce culling of swine females. The causes of sudden death in sows should be better understood. Case reports of mesenteric osseous choristomas are rare in pigs, however it is not possible to assert if its occurrence is low, since few sudden deaths in sows are investigated.